THE ENGLISH TERMS USED IN HOTELS AND TOURISM PLACES AND THEIR CORRESPONDENCES IN INDONESIAN - Rahayu, Acep (PEOPLE: International Journal of Social Sciences, 2017)
The research motivation is to find out proper Indonesian terms used for hotel and tourism facilities, and the objectives are to find out the correspondences of the English terms used in hotels and tourism places in Bandung, West Java Indonesia, and the strategies used by foreign tourists in understanding the Indonesian terms used in those places. The research Methodology used were observation, interview and questionnaire. My research Findings are as follows: -some of the English terms used in hotels and tourism places have their correspondences in Indonesian, and some of the English terms do not have their correspondences in Indonesian, - some foreign tourists used a dictionary in understanding the Indonesian terms used in hotels and tourism places, -some of them directly asked questions to Indonesian people they met and some just guessed the meaning of the terms. In conclusion, there are some English terms which have correspondences in Indonesian, but some do not have correspondences in Indonesian, and searching for meaning, asking directly to the people they met and guessing the meaning were the strategies used by the international used to understand the Indonesian terms used at hotels and tourism places in Indonesia. The research outcomes are firstly, recommendation for English language training for hotel and tourism place staff to reduce cultural and language misunderstanding, and secondly, creating and applying proper Indonesian terms or correspondences for English terms at hotels or tourism places in Indonesia. For academicians, similar research to this should be further enhanced for the benefits of linguistics development; hence, investigating further research in similar subject should be administered.The future scopes of this research are to introduce and overcome cultural awareness and language barriers for the hotels and tourism developers.